EPISTEMOLOGI FILSAFAT ISLAM DAN MASALAH KEMUNDURAN PERADABAN ISLAM - Rusyd, Ibnu (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Reading Islamic history and civilization and contemporary conditions affected by irrational religious narratives, the decline of Muslim society, conflicts, and violence prove that the decline and backwardness of civilization are still continuing in Islamic world. Various formula are offered to revive Islamic civilization. However, instead of compiling a formula with a strong scientific foundation, the response has been increasingly ideological and political from time to time. At the same time, unfortunately, the Muslim community used heretics and prohibitions to purge Islam’s only scientific and rational heritage, philosophy, from the stage of civilization. Through an interdisciplinary approach and critical discourse analysis methods utilizing empirical and literature to reveal the urgency of philosophy as an important tradition related to advance quality of civilization, this research findings important results are; First, Islamic philosophy deals with the creation of scientific and humanist culture which becomes basis progress of civilization. Second, after forbidden by Sunni orthodox which made political alliences with rulers, Islamic philosophy lost its influence, and gradually Islamic civilization declined. Third, decline that continue to this day is the result of the position of Islamic philosophy which has not been sufficiently revitalized in Muslim societies.